Prevalência de sarcopenia em idosas com disfunções do assoalho pélvico - Silva, Rávida da Rocha (2019)
Sarcopenia and pelvic floor dysfunctions can commonly arise during aging, affecting negatively the functionally important architectural parameters in the muscles of the limbs and trunk, leading to decreased quality of life, mobility and increased adverse health events. The objective was to estimate the prevalence of sarcopenia in elderly women with pelvic floor disorders. This is a cross-sectional study, developed in two outpatient clinics specialized in urogynecology in the city of Fortaleza, from February to September 2019. The sample consisted of 217 elderly women. Those aged 60 years or over with a confirmed diagnosis of pelvic floor dysfunction were included. Elderly women with cognitive alterations, amputations or fractures in the upper and / or lower limbs that prevented the performance of the proposed tests were excluded. For data collection, the following instruments were used: Mini Mental State Examination, form containing sociodemographic, clinical and gynecological-obstetric data, anthropometric and sarcopenia assessment. The data were grouped using Research Electronic Data Capture and analyzed using the statistical program Statistical Package for the Social Sciences, version 24.0. In the numerical variables, the data were presented as mean and standard deviation. Regarding categorical variables, the data were exposed in terms of frequency and prevalence rate, in order to investigate associations between sociodemographic, clinical, gynecological obstetric characteristics, diagnosis of pelvic floor dysfunction and sarcopenia, using the Chi-square test Pearson and Fisher's Exact Test. Mann-Whitney U test was used to analyze the characteristics of the participants, verifying the non-adherence of the data to the Gaussian distribution. The project was submitted to the research ethics committee of the services where the data were collected, with approval under opinions No. 3,159,390 and No. 3,270,489. As for pelvic floor dysfunctions, most elderly women had urinary incontinence (n = 166; 76.5%), followed by pelvic organ prolapse (n = 156; 71.9%) and anal incontinence (n = 9; 4 ,1%). Of the 217 elderly women, 121 (55.8%) had no sarcopenia, 71 (32.7%) had probable sarcopenia, 23 (10.6%) confirmed sarcopenia and 2 (0.9%) severe sarcopenia. There was an association between the presence of sarcopenia and higher mean age (p = 0.029) and menopause time (p = 0.001), family history of pelvic floor dysfunction (p = 0.037), physical exercise (p = 0.044), lower weight (p <0.001), waist circumference (p <0.001), body mass index (p <0.001) and calf circumference (p <0.001). Regarding the severity of the dysfunctions, the most severe stages of pelvic organ prolapse were associated with sarcopenia (p = 0.002). The data found are of transversal interest in health and bring information hitherto unknown to the region of the study and to gerontology, also providing subsidies for the development of intervention research, actions to prevent sarcopenia and health promotion for the elderly.